COLLABORATIVE-HUB SEBAGAI UPAYA MENGENANG KAWASAN HARMONI - Dewi, Jessica Christiani; Sutisna, Sutarki (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
The Harmoni area is an area that is getting busier every day and is an active commercial area. This area has a collection of history that cannot be felt by the current generation. Some points in this place are very dark and vulnerable when all offices and shops are closed at night. Many old buildings are empty and abandoned. This area has the potential to become an old city area that provides a new sense of nostalgic space for each generation and can also function as a place of entertainment for the surrounding and outside communities. The historical value of this area is increasingly eroded, which should be a lesson for the community about how the city of Jakarta got here. This study discusses efforts to preserve abandoned historical areas through continuous restoration in accordance with technological advances and the times to suit the current generation by conducting observations, collecting and analyzing data at the location. By adapting activities in places that have been done before, such as including public spaces, gathering places, or party places and utilizing the potential of areas that have good accessibility considering that this area has the largest transit point in Jakarta so that the area can keep up with the times. This activity is implemented in an empty land located on Jalan Juanda which is within a radius of 150 meters from the Harmoni node. This implementation aims to restore the character of the area that has been degraded so that it comes back to life and is crowded with visitors. Keywords: harmoni; location; public area; transit Abstrak Kawasan Harmoni merupakan daerah yang semakin ramai setiap hari dan merupakan area komersial yang aktif. Wilayah ini memiliki sekumpulan sejarah yang tidak dapat dirasakan oleh generasi saat ini. Beberapa titik di tempat ini sangat gelap dan rawan pada saat semua perkantoran dan toko tutup di malam hari. Banyak bangunan lama yang kosong dan terbengkalai. Wilayah ini berpotensi menjadi kawasan kota lama yang memberikan perasaan ruang nostalgia baru bagi setiap generasi dan juga dapat berfungsi sebagai tempat hiburan bagi komunitas sekitar dan luar. Nilai sejarah dari wilayah ini semakin tergerus, yang seharusnya dapat menjadi pelajaran bagi masyarakat tentang bagaimana kota Jakarta sampai di sini. Penelitian ini membahas tentang upaya untuk melestarikan wilayah bersejarah yang telah ditinggalkan melalui pemulihan yang berkesinambungan sesuai dengan kemajuan teknologi dan zaman agar sesuai dengan generasi sekarang dengan cara melakukan observasi, mengumpulkan dan menganalisis data pada lokasi. Dengan mengadaptasi aktivitas-aktivitas pada tempat-tempat yang pernah dilakukan sebelumnya seperti memasukan ruang publik, tempat berkumpul, atau tempat berpesta serta memanfaatkan potensi dari kawasan yang memiliki aksesibilitas yang baik mengingat kawasan ini memiliki titik transit terbesar di Jakarta sehingga kawasan dapat mengikuti perkembangan zaman. Aktivitas ini dterapkan dalam lahan kosong yang berlokasi di Jalan Juanda yang berada dalam radius 150 meter dari simpul Harmoni. Penerapan ini bertujuan untuk mengembalikan kembali karakter kawasan yang telah mengalami degradasi agar kembali hidup dan ramai pengunjung.